Fatigue Life Assessment for Metallic Structure: A Case Study of Shell Structure under Variable Amplitude Loading - M. M., Rahman; A. K., Ariffin; S. M., Beden; S., Abdullah (Asian Network for Scientific Information, 2008)

(untitled)
his study presents an analysis technique to asses the fatigue life of a shell structure under variable amplitude loadings (VAL). For this purpose, the finite element analysis technique was used for the simulation works. The life prediction results are useful for improving the component design methodology at the early developing stage especially for shell structures such as a pressure vessels or pipelines analysis. The fatigue life prediction was performed using the finite element based fatigue analysis codes. In addition the ability of stress-life (S-N) and strain-life (e-N) approaches to correlate and predict life are examined according to the different damage and failure rules. Numerical life prediction results (S-N and e-N) of shells under VAL, as well as Constant Amplitude Loading (CAL) are presented and discussed. The effect of the mean stress, surface finish and the shell thickness are studied and discussed as apart of the interactions between geometries, loadings and materials. The simulation results showed that more studies on the shell structure need to be performed in order to obtain more accurate fatigue life.